Understanding the Challenges and Factors Contributing to Learning Pace Differences in Mathematics Among Grade Seven Students at Osmeña Colleges - Atenas, Dennis (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study investigated the factors affecting mathematics learning pace among Grade 7 students at Osmeña Colleges Junior High School during the academic year 2023–2024. Anchored on Cognitive Load Theory, Vygotsky’s Zone of Proximal Development, and Self-Determination Theory, the study examined the demographic, psychological, instructional, and environmental influences contributing to differences in students’ mathematics learning progression. A descriptive quantitative research design was employed using a structured survey questionnaire composed of closed-ended items. The respondents consisted of 28 Grade 7 students selected through purposive and random sampling procedures from a population of 30 learners. Data were analyzed using percentage distribution and weighted mean. The findings revealed that most respondents were early adolescents, with the majority aged 13 years old. Students encountered difficulties related to distractions during class, solving word problems, understanding lessons delivered too quickly, and keeping pace with classroom instruction. Emotional and motivational factors such as mathematics anxiety, low self-confidence, and fear of failure also affected learning pace, although many students remained motivated to improve their mathematics skills. Instructional strategies involving visual aids, guided problem-solving, and teacher feedback positively supported learning, while interactive and student-centered approaches were only moderately utilized. Environmental factors such as availability of study spaces, access to learning materials, family encouragement, and household responsibilities likewise influenced students’ learning experiences. Respondents identified one-on-one tutoring, flexible assessment time, and technology-supported learning interventions as beneficial strategies for improving mathematics performance. The study concluded that mathematics learning pace is shaped by interconnected demographic, psychological, instructional, and environmental factors. It recommended the implementation of differentiated and scaffolded instruction, problem-based and collaborative learning approaches, social-emotional support, strengthened home–school partnerships, and Multi-Tiered System of Supports (MTSS) interventions to address diverse learner needs and promote equitable mathematics learning opportunities. The study supports Sustainable Development Goal (SDG) 4: Quality Education by promoting inclusive and learner-centered instructional practices, as well as SDG 10: Reduced Inequalities through equitable educational support for students with varying learning abilities. The findings contribute to educational sustainability by encouraging adaptive teaching practices, improved student well-being, and inclusive learning environments that strengthen long-term academic development and institutional effectiveness.